Nursing Workload and Patient Dependency: Strategies for Staffing Optimization and Resource Allocation - Setyaningrum, Ikawati (Universitas Syiah Kuala, 2024)
This study explores strategies for optimizing staffing and resource allocation based on nursing workload and patient dependency in healthcare settings. Through a comprehensive literature review of ten selected articles, the research highlights the critical importance of aligning nursing resources with patient needs to enhance patient outcomes and ensure nurse well-being. The findings consistently demonstrate that higher nurse-to-patient ratios and adequate staffing levels are associated with improved patient outcomes, such as reduced mortality rates, fewer patient safety incidents, and enhanced quality of care. Additionally, the review emphasizes the importance of a balanced skill mix and the competencies of the nursing workforce in delivering effective care, particularly in high-dependency environments. The study underscores the need for healthcare organizations to adopt flexible and dynamic staffing models that can adapt to changing patient needs, especially in the context of global healthcare challenges such as the COVID-19 pandemic. The research also calls for future studies to explore the impact of technology on staffing optimization and to examine the long-term effects of different staffing strategies on patient outcomes and nurse satisfaction.